PROMOSI OBJEK WISATA ALAM PULAU BELIBIS DAN TAMAN PRAMUKA DI KOTA SOLOK MELALUI MEDIA WEBSITE - PUTRI MAYASARI, Drs. Syafwan, M.Si., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
The purpose of final project: (1) promoting the natural tourism object, Pulau Belibis and Taman Pramuka for public. The promotion that have done by the local government is not successful. Besides, this this tourism object is very interesting to be visited. (2) promoting the natural tourism object by using the effective media for native and tourist who comes to Solok, and they can know and visit that natural tourism object. Data that have gotten in make this promotion are by doing the observation and direct interview. The final project product is a website as the principal media that consist of information about that natural tourism object.Keywords: website, promotions, Natural attractions Pulau Belibis and Taman Pramuka.